2016
DOI: 10.11611/yead.282052
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of International and Domestic Acquisitions: A Literature Review

Abstract: International Aquisitions (IAs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…This synergy from an acquisition reflects on the firm's financial tables (Selçuk, Köksal and Yılmaz, 2016) as well as the stock prices positively (Çakır and Gülcan, 2012). However, there is also a view that stock prices should not be the only determinant of success in acquisitions since short-term reactions and long-term returns may contradict (Genc, 2016). Target companies have their own motivations to engage in acquisitions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This synergy from an acquisition reflects on the firm's financial tables (Selçuk, Köksal and Yılmaz, 2016) as well as the stock prices positively (Çakır and Gülcan, 2012). However, there is also a view that stock prices should not be the only determinant of success in acquisitions since short-term reactions and long-term returns may contradict (Genc, 2016). Target companies have their own motivations to engage in acquisitions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Bendaş (2015) argues that the synergy from the acquisition may lead to economies of scale if acquisition occurs between firms, which operate in the same industry (horizontal acquisition). In a similar vein, Genc (2016) argues that the success of acquisition is not the same for domestic and international deals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although there are studies that found a positive effect of M&As (Chari et al, 2010;Tao et al, 2017), the majority of studies view M&As as detrimental to the firm performance acquisitions (Agrawal et al, 1992;Billet & Qian, 2008;Spyrou & Siougle, 2007). Increase use of M&As despite the high failure rates creates a paradox in the understanding of M&As (Genç, 2016). Agency problems (Kogut & Zander, 1993), CEO overconfidence (Malmendier & Tate, 2008), information asymmetry (Fu et al, 2013) are among the factors that have been used to explain the failure in acquisitions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although international acquisition has become the preferred mode of international growth over greenfield investments (Vermeulen & Barkema, 2001), existing empirical work on the impact of acquisitions on CEO compensation focuses on domestic acquisitions (Cesari, Gönenç, & Ozkan, 2016; Datta, Iskandar‐Datta, & Raman, 2001; Girma, Thompson, & Wright, 2006; Grinstein & Hribar, 2004). International acquisitions differ fundamentally from domestic ones in terms of both the driving factors as well as post‐acquisition integration issues, which are affected by heterogeneous cultures and institutions, sovereign and exchange risks, and other complications (Genc, 2016). There are some studies that demonstrate those differences.…”
Section: Introductionmentioning
confidence: 99%